Native language interference in learning english as foringn langauge: an analysis of written material produced by spanish speaking studets in senior high school classes. - Sánchez, Penélope (2010)
Foreign language education is taking a new turn, from seeing mistakes and errors as obstacles to tools that can help to predict and be carefully analyzed in order to understand the construction of a new language system. When a learner is acquiring a foreign language his native language will have an effect on the production of the language being learned; i.e. interference. Lott (1983:256) defines interference as “errors in the learner’s use of the foreign language that can be traced back to the mother tongue.” Interference has a negative denotation; that is, the more the native and the target languages are different from each other, the more mistakes and errors will occur. The effect of interference can be on any aspect of language: grammar, vocabulary, accent, spelling and others.